Serum clinical biochemical markers of Hy-Line W-36 laying hens under the influence of increased stocking densities in cages of multilevel batteries - Y. V. Osadcha; M. I. Sakhatsky; R. O. Kulibaba (Regulatory Mechanisms in Biosystems, 2021)
Today, the organism of hens is constantly exposed to numerous technological stressors in the conditions of industrial poultry farming, the least studied of which are long-term, which can cause the development of chronic stress. One of such stressors is the increased stocking density of hens, which is also a way of saving resources in egg poultry and is often used by producers to obtain more eggs per 1 m2 of poultry area. The aim of this study was to examine the effect of overcrowding, as a factor of chronic stress development, on the body of hens of a modern high-performance cross, which is necessary to select the best ways to keep them. Four groups of hens were formed for this purpose, which were kept at different stocking densities, according to European standards, Ukrainian standards and with increasing overcrowding. In this way, the gradually increasing intensity of the technological stressor was modeled. Long-term keeping of laying hens at high stocking density did not affect the content in the serum of total protein, albumin, urea and cholesterol, which were within the physiological norm. It was found that the increase in the stocking density of hens to Ukrainian standards, compared to the European, was accompanied by an increase in the activity of lactate dehydrogenase in the serum of their blood. With an increase in stocking density above European and Ukrainian standards, namely to 25.3 birds/m2, there was an increase in the activity of three enzymes – lactate dehydrogenase, aspartate aminotransferase and gamma-glutamyltransferase. It is proved that further overcompaction of hens to 26.7 birds/m2 is accompanied by an increase in serum glucose, creatinine, as well as a decrease in the ratio of calcium and phosphorus, which was confirmed by an increase in alkaline phosphatase activity. Also, increased activity of aspartate aminotransferase, lactate dehydrogenase and gamma-glutamyltransferase was observed. Thus, the main effects of chronic stress caused by prolonged keeping of hens at high stocking densities are reflected in the biochemical parameters of their serum, namely in the increase of glucose, creatinine, enzyme activity, as well as the violation of the ratio of calcium and phosphorus.